Network disruption detected in PY (Paraguay) - Voidly (2026)
CRITICAL severity disruption detected in Paraguay. Confidence: 75%. Data sourced from IODA.
Network Disruption Incident ID: PY-2026-0001
Keywords: internet disruption; PY; disruption; critical